Effect of sex hormones level on the external genital tract infection in pregnant and non- pregnant women in Dhi Qar governorate, Iraq - Abdul wehab wajeh , Safa; Abdul Hussein , Basim; Abdul Razzaq, Mohanad (University of Thi-Qar Journal of Science, 2019)
The current study was conducted in Dhi Qar governorate, Iraq to determine the main types of microorganisms that cause female genital tract infection and the extent of the effect of the level of sex hormones (prolactin, progesterone, estrogen) on the presence of infection , 245 samples were collected for both vaginal swabs and blood (where take a vaginal swab and blood from every woman) , where 150 women were pregnant and 95 women non-pregnant women , aged 16-45 years . Among non-pregnant women, most were women who had a reproductive tract infection within the leuteal phases , where our study included 58 women at leuteal phase , 20 women were in follicular phase , 17 women within ovulation phase of the menstrual cycle . The study showed that Candida albicans , Staphylococcus aureus , Escherichia coli , Gardnerella vaginalis , Klebsiella pneumonia , Staphylococcus epidermids , Enterobacter cloaceae were isolated from women in follicular phase , the diversity of infections was lower in women in the ovulation stage, where they were isolated only Candida albicans , Staphylococcus aureus , Escherichia coli , Gardnerella vaginalis ,and from women with leuteal phase was obtained Candida albicans , Staphylococcus aureus , Escherichia col ,Gardnerella vaginalis , Klebsiella pneumonia , Staphylococcus epidermids , Proteus mirabilis, Pseudomonas aeruginosa , the precence of all type of pathogens in our study was associated with elevated estrogen and progesterone levels except the growth of Staphylococcus epidermids , Proteus mirabilis, Pseudomonas aeruginosa , Enterobacter cloaceae was associated with normal range of each hormones,as for the prolactin hormone did not have a clear effect as the levels ranged between natural and high for all women in the three phases. Pregnancy was accompanied by high levels of estrogen, progesterone and prolactin hormones, this is accompanied with existence Candida albicans , Staphylococcus aureus , Escherichia coli , Gardnerella vaginalis , Klebsiella pneumonia , Streptococcus agalactiae , Trichomonas vaginalis.